Acceptability of a mental health care pathway to address dementia risk factors in primary care settings: A qualitative study: Developing topics. (7th December 2020) - McAiney, Carrie A; Berry, Camryn; Parascandalo, Fiona; Kates, Nick; Saperson, Karen; Dham, Pallavi; Malik, Noor; Rajji, Tarek K
Abstract: Background: Given the projected increases in dementia prevalence across the world, it is imperative that we identify and mitigate the potential impacts of reversible risk factors for developing dementia. Depression, anxiety and mild cognitive impairment (MCI) are examples of such risk factors. However, despite their relatively high prevalence rates among those age 60 and over, these conditions often go unrecognized and untreated. A growing body of evidence suggests that evidence‐based interventions in primary care can increase detection and treatment rates of these conditions, and may help to prevent or prolong the development of dementia. This presentation reports on qualitative data collected as part of a longitudinal cohort study examining the implementation and effectiveness of an Integrative Care Pathway (ICP) for depression, anxiety and MCI in primary care settings. Method: A qualitative descriptive design was used to examine the acceptability of the ICP by primary care providers. Two sets of focus groups were conducted with five participating primary care practices during the study. Participants varied by practice and included family physicians, nurses, allied health professionals, and administrative staff. Focus groups were audio‐recorded, transcribed verbatim, and analyzed using conventional content analysis. Result: The findings indicate that providers had mixed reactions in terms of the acceptability of the ICP. The fact that the ICP was evidence‐based was a strength of the pathway and gave providers and patients reassurance regarding the management of depression, anxiety and MCI. However, the realities of primary care practice, particularly in terms of time constraints, indicated the need for flexibility in how the ICP is applied. Conclusion: Having access to evidence‐based resources can support primary care providers in managing mental health risk factors for dementia. However, resources need to reflect the culture and practices of primary care settings in order for them to be acceptable to providers.